1999
DOI: 10.1021/je9803025
|View full text |Cite
|
Sign up to set email alerts
|

Infinite-Dilution Activity Coefficients of Polar and Nonpolar Solvents in Solutions of Hyperbranched Polymers

Abstract: Infinite-dilution activity coefficients are measured for several polar and nonpolar solvents in hyperbranched polymers using inverse gas chromatography in the temperature range 40-160 °C. Two kinds of polymers are studied: comb polymers and dendritic polymers. The combs are poly(styrene-co-maleic anhydride) with alkyl side chains of different lengths (C12, C22). The solvents are: acetone, toluene, tetrahydrofuran (THF), and chloroform. Solvent solubility in the combs depends on the ratio between the polar back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Polese et al reported measurements of infinite-dilution activity coefficients for polar and nonpolar solvents in comb polymers and polypropylenimine dendrimers of generation 2 to 5 [40]. Solvent activity coefficients at infinite dilution change with respect to the dendrimer generation number, reaching a minimum at generation 4 in the temperature range 333 to 413 K [40].…”
Section: Dendritic Polymer Solutions ± the Role Of Polymer Branching mentioning
confidence: 99%
See 1 more Smart Citation
“…Polese et al reported measurements of infinite-dilution activity coefficients for polar and nonpolar solvents in comb polymers and polypropylenimine dendrimers of generation 2 to 5 [40]. Solvent activity coefficients at infinite dilution change with respect to the dendrimer generation number, reaching a minimum at generation 4 in the temperature range 333 to 413 K [40].…”
Section: Dendritic Polymer Solutions ± the Role Of Polymer Branching mentioning
confidence: 99%
“…Solvent activity coefficients at infinite dilution change with respect to the dendrimer generation number, reaching a minimum at generation 4 in the temperature range 333 to 413 K [40]. Due to the exothermic formation of hydrogen bonding, alcohols can form hydrogen bonds with the dendrimer more easily at low temperatures and hence the solubility decreases with increasing temperature [40]. Since Polese et al used dendrimers with a basic character, slightly acidic solvents showed better solvent qualities than others (THF, toluene, ethyl acetate).…”
Section: Dendritic Polymer Solutions ± the Role Of Polymer Branching mentioning
confidence: 99%
“…poly(styrene-co-maleic anhydride), or C 22 esterified poly(styrene-co-maleic anhydride)], using IGC were presented [32,33]. The values of the mass-fraction activity coefficient for these polymers X 1 12 were (at very high temperatures T > 360 K) from 3 to 40.…”
mentioning
confidence: 99%
“…As opposed to our findings, which showed an increase in solubility with increasing temperature, it is reported that due to the exothermic formation of hydrogen bonding, alcohols can form hydrogen bonds with dendrimers more easily at lower temperatures and hence solubility decreases with increasing temperature. [41] Temperature dependent IR measurements could be used to prove the assumption that the weakening of H bonds is responsible for structural changes in the ester diol. The IR spectra of the pure hyperbranched polyester, the pure ester diol and the blend of ester diol with 1% of the hyperbranched polyester in the full mid-infrared spectral region at 25 8C are given in Figure 6.…”
Section: Resultsmentioning
confidence: 99%